Newspaper markets and municipal politics: how audience and congruence increase turnout in local elections. Issue 1 (2nd January 2019) - Kübler, Daniel; Goodman, Christopher
ABSTRACT: Media coverage of politics is widely considered essential to political participation. However, studies on local elections do not yet generally take the effect of the media environment into account. This article posits that the territorial fit between newspaper markets and municipal boundaries makes citizens' exposure to locally relevant news more likely. We use fine-grained data on newspaper readership in order to assess the effect of the territorial structure of the newspaper market on turnout in municipal elections in Switzerland. The analysis shows that newspaper audience in a municipality and the congruence of newspaper markets with municipal territories both have substantial positive effects on levels of turnout in municipal elections. The findings suggest that future research on local political behavior should better acknowledge the influence of the media environment – which can be adequately measured by newspaper audience and congruence. Implications are that current structural changes in the media system bear threats to local democracy via the territorial upscaling of media markets.